Functional Diversification of Fungal Glutathione Transferases from the Ure2p Class. (22nd November 2011) - Thuillier, Anne; Ngadin, Andrew A.; Thion, Cécile; Billard, Patrick; Jacquot, Jean-Pierre; Gelhaye, Eric; Morel, Mélanie
Abstract : The glutathione-S-transferase (GST) proteins represent an extended family involved in detoxification processes. They are divided into various classes with high diversity in various organisms. The Ure2p class is especially expanded in saprophytic fungi compared to other fungi. This class is subdivided into two subclasses named Ure2pA and Ure2pB, which have rapidly diversified among fungal phyla. We have focused our analysis on Basidiomycetes and used Phanerochaete chrysosporium as a model to correlate the sequence diversity with the functional diversity of these glutathione transferases. The results show that among the nine isoforms found in P. chrysosporium, two belonging to Ure2pA subclass are exclusively expressed at the transcriptional level in presence of polycyclic aromatic compounds. Moreover, we have highlighted differential catalytic activities and substrate specificities between Ure2pA and Ure2pB isoforms. This diversity of sequence and function suggests that fungal Ure2p sequences have evolved rapidly in response to environmental constraints.